Frequency of Common Pathogens Isolated from Open Fractures of the Extremities and their Antimicrobial Sensitivity Pattern. (Journal of Pakistan Orthopaedic Association, 2021)
Objective: To determine the frequency of micro organisms in open fractures of the extremities and their sensitivity pattern to the commonly used antibiotics.Methods: This descriptive study was conducted in the Department of Orthopaedic Surgery Nishtar Medical University Hospital Multan. The duration of our study extended from 29th June 2019 to 5th July 2020. Patients of either gender and age 18 to 60 years with open fractures meeting the inclusion criteria were enrolled in our study. Wound swabs were taken with Levine technique before surgical debridement and sent to laboratory for Gram staining and culture and sensitivity of the microbial agents. Post stratification comparison of important variables were done and P value was calculated with the help of Chi-square test. ( P